Evolutionary History of Bacteriophages in the Genus Paraburkholderia - Pratama, Akbar Adjie; Chaib De Mares, Maryam; van Elsas, Jan Dirk (Frontiers in Microbiology, 2018)
The genus Paraburkholderia encompasses mostly environmental isolates with diverse predicted lifestyles. Genome analyses have shown that bacteriophages form a considerable portion of some Paraburkholderia genomes. Here, we analyzed the evolutionary history of prophages across all Paraburkholderia spp.. Specifically, we investigated to what extent the presence of prophages and their distribution affect the diversity/diversification of Paraburkholderia spp., as well as to what extent phages coevolved with their respective hosts. Particular attention was given to the presence of CRISPR-Cas arrays as a reflection of past interactions with phages. We thus analyzed 36 genomes of Paraburkholderia spp., including those of 11 new strains, next to those of three Burkholderia species. Most genomes were found to contain at least one prophage sequence. The highest number was found in Paraburkholderia sp. strain MF2-27; the nine prophages found amount to up to 4% of its genome. Among all prophages, potential moron genes (e.g. DNA adenine methylase) were found that might be advantageous for host cell fitness. Co-phylogenetic analyses indicated the existence of complex evolutionary scenarios between the different Paraburkholderia hosts and their prophages, including short-term co-speciation, duplication, host-switching and phage loss events. Analysis of the CRISPR-Cas systems showed a record of diverse, potentially recent, phage infections. We conclude that, overall, different phages have interacted in diverse ways with their Paraburkholderia hosts over evolutionary time.